Assessing the burden of pneumonia using administrative data from Malaysia, Indonesia, and the Philippines - Soraya Azmi; Syed Mohamed Aljunid; Namaitijiang Maimaiti; Al-Abed Ali; Amrizal Muhammad Nur; Madeleine De Rosas-Valera; Joyce Encluna; Rosminah Mohamed; Bambang Wibowo; Kalsum Komaryani; Craig Roberts (International Journal of Infectious Diseases, 2016)
Objectives: To describe the incidence, mortality, cost, and length of stay (LOS) of hospitalized community-acquired pneumonia (CAP) and hospital-acquired pneumonia (HAP) in three Southeast Asian countries: Malaysia, Indonesia, and the Philippines. Methods: Using Casemix system data from contributing hospitals, patients with International Classification of Diseases 10th revision (ICD-10) codes identifying pneumonia were categorized into CAP or HAP using a logical algorithm. The incidence among hospitalized patients, case fatality rates (CFR), mean LOS, and cost of admission were calculated. The population incidence was calculated based on Malaysian data. Results: For every 100 000 discharges, CAP and HAP incidences were 14 245 and 5615 cases, respectively, in the Philippines, 4205 and 2187, respectively, in Malaysia, and 988 and 538, respectively, in Indonesia. The impact was greatest in the young and the elderly. The CFR varied from 1.4% to 4.2% for CAP and from 9.1% and 25.5% for HAP. The mean LOS was 6.1–8.6 days for CAP and 6.9–10.2 days for HAP. The cost of hospitalization was between USD 254 and USD 1208 for CAP and between USD 275 and USD 1482 for HAP. Conclusions: The burden of CAP and HAP is high. Results varied between the three countries, likely due to differences in socio-economic conditions, health system differences, and ICD-coding practices.